Drivers of the Adoption of E-Government Services in the deliverance of healthcare services in Federal Health Institutions - Archibong E. Ironbar; Pius U. Angioha; Ijim A. Uno; Julius A. Ada; Francis E. Ibioro (ARRUS Journal of Engineering and Technology, 2021)
The study examines Drivers of the Adoption of E-Government Services in the deliverance of Healthcare services in Federal Health Institutions. the study adopts drivers such as perceived Usefulness and perceived ease of use and their influence in the adoption of E-Government Services in the deliverance of Healthcare services in Federal Health Institutions. The survey research design was adopted in collecting 400 sample from administrative staff of the University of Calabar Teaching Hospital, Calabar using the purposive sampling. The sample size was determined using Taro Yamane sample size determinant technique. The questionnaire was the instrument of data collection. Data collected was analyzed using simple regression analysis at 0.05 confidence level. Result revealed that Perceived usefulness significantly influence the adoption of E- Governance Services in the deliverance of Healthcare services in Federal Health Institutions (R-value of 0.176a). Also result revealed that Perceived Ease of Use significantly influence the adoption of E- Governance Services in the deliverance of Healthcare services in Federal Health Institutions (R2 –value of .018). based on this result the study recommends amongst others that there is need for efforts to improve this basic infrastructure by the government should be strengthened both in terms of coverage and quality